Disentangling artificial and natural benthic weathering in organic rich Baltic Sea sediments - Fuhr, Michael; Wallmann, Klaus; Dale, Andrew W.; Diercks, Isabel; Kalapurakkal, Habeeb Thanveer; Schmidt, Mark; Sommer, Stefan; Böhnke, Stefanie; Perner, Mirjam; Geilert, Sonja (Frontiers in Climate, 2023)
Enhanced mineral dissolution in the benthic environment is discussed as a potential technique for ocean alkalinity enhancement (OAE) to reduce atmospheric CO2 levels. This study explores how biogeochemical processes affect the dissolution of alkaline minerals in surface sediments during laboratory incubation experiments by introducing dunite and calcite to organic-rich sediments from the Baltic Sea under controlled oxic conditions. The sediment cores were incubated with Baltic Sea bottom water. Findings reveal that the addition of calcite increased the benthic alkalinity release from 0.4 µmol cm-2 d-1 to 1.4 µmol cm-2 d-1 as well as other weathering. However, these enhanced fluxes weakened after approximately four weeks yet still higher than the unamended controls. Microbial activity appeared to be the primary driver for lowering pore water pH and thus enhanced weathering. In several sediment cores, pH profiles taken at the start of the experiments indicated activity of Beggiatoa spp, which was verified by RNA-profiling of 16S rRNA genes. The pH profiles transitioned to those commonly associated with the activity of cable bacteria as the experiments progressed. The metabolic activity of cable bacteria would explain the significantly lower pH values (~5.6) at sediment depths of 1-3 cm, which would favor substantial calcite dissolution. However, a high abundance of cable bacteria was not reflected in 16S rRNA sequence data. Total alkalinity (TA) fluxes in these cores increased by a factor of ~3, with excess TA/calcium ratios indicating that the enhanced flux originated from calcite dissolution. The dissolution of dunite or the potential formation of secondary minerals could not be identified due to the strong natural flux of silicic acid, likely due to biogenic silica dissolution. Furthermore, no accumulation of potentially harmful metals such as nickel was observed, as highlighted as a potential risk in other studies concerning OAE. Given the complexity of sediment chemistry and changes of the benthic conditions induced by the incubation, it remains challenging to distinguish between natural and enhanced mineral weathering. Further investigation, including the identification of suitable tracers for mineral dissolution, are necessary to assess the feasibility of benthic weathering as a practical approach for OAE and climate change mitigation.